Answer:
second option
third option
fifth option.
Step-by-step explanation:
We have the slope of the line: [tex]m=\frac{2}{3}[/tex]
and we can see that the line passes through the points (1, 2) and (4, 4)
We can use the point slope equation:
[tex]y-y_{0}=m(x-x_o)[/tex]
first, we use the first point (1, 2) and we define [tex]x_0=1[/tex] and [tex]y_0=2[/tex]. Substituting these values along with the value of the slope:
[tex]y-2=\frac{2}{3} (x-1)[/tex] which is the second option
Now, using the second point (4, 4) and defining [tex]x_0=4[/tex] and [tex]y_0=4[/tex], using again the point slope equation [tex]y-y_{0}=m(x-x_o)[/tex], we get:
[tex]y-4=\frac{2}{3}(x-4)[/tex] which is the third option
finally, we can solve the previous equation for y:
[tex]y=\frac{2}{3}(x-4)+4\\ \\y=\frac{2}{3}x-\frac{2}{3}(4)+4\\ \\y=\frac{2}{3}x-\frac{8}{3} +4\\\\y=\frac{2}{3}x+\frac{4}{3}[/tex]which is the fifth option.